Perilaku memiliki tabungan pendidikan anak - Christine Gracia Setyawati; Supramono Supramono (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2020)
A form of parental responsibility for the continuity of their children's education is to prepare children's education funds from early ages. This study aims to examine the determinants of the intention to have children's education savings including; financial knowledge, risk tolerance, future financial orientation, social influence and their effect on the behavior of having children's education funds. The sample of this study involved 192 parents who had children under five years old and or children who are currently attending school education in Sidorejo District, Salatiga. Data was collected by the field survey method and analyzed using Structural Equation Modeling (SEM). The study results showed that financial knowledge, future orientation and social influence affected the intention to have educational savings. Further, the intention affected the behavior of having educational savings. However, the facilitating conditions such as the existence of bank institutions do not strengthen the influence of intention on behavior. This study contributes by not only broadening insights on education savings from a behavioral perspective but also by offering practical implications for policy makers and banking institutions in order to encourage public interest in having education savings so that the sustainability of children's education in terms of financing will be more secure.